The regulation of water services in the EU - Ralf Boscheck; Judith C. Clifton; Daniel Díaz-Fuentes; Mark Oelmann; Christoph Czichy; Monica Alessi; Sébastien Treyer; Janet Wright; Martin Cave (Intereconomics, 2013)
The European Commission's proposal for a Directive on the award of concession contracts has sparked vigorous public debate and intense opposition. This Directive is controversial because of the nature of the policy it proposes and because the sectors involved are highly sensitive. This Forum examines the weaknesses of the Commission's proposal and presents an overview of the current issues in water regulation and the provision of water services. The authors analyse the regulation of natural monopolies, water efficiency and upstream competition in the water industry.
Keywords: 330; Wasserversorgung; Wasserpreis; Wettbewerb; Wasserpolitik; EU-Staaten